Prospective cross sectional study on anatomical variation with special emphasis on critical anatomical landmark in patients undergoing multi detector computed tomography of paranasal sinuses: Anatomical variation in CT PNS (GAIMS Journal of Medical Sciences, 2022)
Introduction: Paranasal sinuses are best evaluated by multi-detector computed tomography. Evaluation of sphenoid sinus pneumatization, lamina papyracea, onodi cell, cribriform plate, types of optic canal and supraorbital pneumatisation  are useful for evaluation of the surgical anatomy of paranasal sinuses for the radiologist which guides the surgeon to take a correct approach for surgery without major complications of crucial structures. CT is recently used as a investigation of choice in the assessment of the paranasal sinuses and surrounding structures.Aims and Objective:  To study the types of anatomical variation of paranasal sinuses and osteomeatal complex and clinical importance of these various of paranasal sinus on pre-operative computed tomography.Materials and Methods: Over a period of 18 months, 104 patients referred for CT scan of PNS region G.K.General hospital were evaluated for the presence of normal variants of the paranasal region. Unenhanced CT of the PNS was performed for these patients in the coronal plane, complemented by axial views in selected cases.Results: Out of 109 patients who fulfilled inclusion criteria were studied from that most common is type II cribriform plate found in  80.7% of patients, Presence of haller cells was noted in 11.01% of individuals. Most of the uncinate process was attached to lamina papyracea in 88.9% individuals. Onodi cell was identified among 41% patients. Depending on the pneumatization of the sphenoid sinus, type I course of optic nerve was most common. Sellar variety of sphenoid sinus was more common observed in 82.5% patients. Presence of supraorbital pneumatization was identified in 72.4% patients among total subjects.Conclusion: The presence of anatomical variants does not indicate a predisposition to sinus pathology but these variations may predispose patients to increased risk of intraoperative complications.